Impacts of e-banking on performance of banks in a developing economy: empirical evidence from Bangladesh - Siddik, Md. Nur Alam; Sun, Gang; Kabiraj, Sajal; Shanmugan, Joghee; Yanjuan, Cui (Journal of Business Economics and Management, 2016)
E-banking has become one of the most popular methods of banking that has experienced a considerable expansion during the last few years. However, there is relative dearth of empirical studies examining the impact of e-banking on performance of banks. Though e-banking is gaining acceptance in Bangladesh, impact of e-banking on bank’s performance is yet to be established. This paper fills this gap. Using panel data of 13 banks over the period of 2003–2013, this study empirically investigated the impact of e-banking on the performance of Bangladeshi banks measured in terms of Return on Equity, Return on Assets and Net Interest Margin. Results from pooled ordinary least square analysis show that e-banking begins to contribute positively to banks’ Return on Equity with a time lag of two years while a negative impact was found in first year of adoption. Empirical findings of this study is of greater significance for the developing countries like Bangladesh because it will invoke the attention of the bank management and policy makers to pursue such policies to expand e-banking. This study also contributes to empirical literatures by reconfirming (or otherwise) findings of previous studies.